KEBERADAAN LADY BIKERS DI KOMUNITAS KLUB MOTOR INDONESIA SEBAGAI KORBAN KEJAHATAN KESUSILAAN DI JALANAN - Arya Maulana Pandhu Pradhana (Jurnal Justiciabelen, 2021)
Seeing the Development and growth of one ot the transportation in Indonesia, namely land transportation, it turns out thatit has significantly increased significantly, including the users of motorized vehicles, especially two-wheeled motorbikes (motorbikes). According to Article 28 E paragraph 3 of the 1945 Constitution, everyone has the right to freedom of association, assembly and expression. So that on that basis some people who have the same hobby and passion about motorbikes establish the Motorcycle Club Community Association in Indonesia. Talking about the Motorcycle Club Community reminds us of a bunch of people who like to act arrogant and anarchic on the road when touring. The existence of Lady Bikers is very interesting to discuss, because with their appearance it makes the Negative Stigma (Arrogance and Anarchy) about the Motorcycle Club Community in the eyes of the cloud community become a little dissolved and is expected to be able to color and give a soft / feminine side in the Motorcycle Club Community which generally consists of Men. On the other hand, the presence of Lady Bikers can lead to Decency Crimes on the Street.